Cenotaph - Mejía Toro, Jorge Mario (Estudios de Filosofía, 2002)
Drawing on Homer, Plato and other poets of our time, the article reflects on the war and the rhetoric that disguises it. The first part goes back, in the Iliad, to the antifuneral that threatens the limit —without return— of cannibalism and reveals the need for the funeral and the significant usage of the funeral meal. The second part uses Menéxeno to criticize the funeral oratory and its common places: autochthony, race, xenophobia, heroism, death for the homeland. Finally, the third part, under the protection of those works, and other shields of the word, denounces the modern inventiveness in the matter of insults to the adversary and suppression of the corpse and the mourning.